Chemical composition of different morphological parts from ‘Dwarf Cavendish’ banana plant and their potential as a non-wood renewable source of natural products - Oliveira, L. (2021)
The study on chemical composition and structure of components from different morphological parts of ‘Dwarf Cavendish’ banana plant (petioles/midrib, leaf blades, floral stalk, leaf sheaths and rachis) have been carried out aiming to evaluate their potential as eventual raw materials for the chemical processing. Macromolecular components were analysed using solid-state NMR, ATR-FTIR and wet chemistry methods. Mineral components were assessed by ICP analysis of ashes obtained after raw material calcinations. It was verified that chemical composition of the studied fractions of banana plant varies significantly. The major extremes were found in the contents of cellulose (37.3% in leaf sheaths and only 15.7% in floral stalk), starch (26.3 in floral stalk and 0.4% in petioles/midrib), lignin (24.3% in leaf blades and 10.5% in rachis) and lipophilic extractives (5.8% in leaf blades and 1.2% in petioles/midrib). All morphologic parts of banana plant contained considerable amounts of ashes (from 11.6 to 26.8%) composed mainly by potassium, calcium and silicium salts. The hemicelluloses in banana plant are proposed to be mainly glucuronoxylan and xyloglucan (from 5.5% in floral stalk to 21.5% in petioles/midrib). Rather significant amount of proteins was found in leaf blades (8.3%). Lignin analysis revealed that it is of HGS type with H:G:S proportion ranged of (5–17):(18–54):(35–71). The significant variation of lignin structure among the different morphological parts of banana plant was highlighted. Results of this study allowed some propositions about possible applications of banana plant residues as non-wood renewable source of natural products.